Study Literature Review: Realistic Mathematics Education Learning on Students’ Mathematical Creative Thinking Ability - Iskandar, Ratu Sarah Fauziah; Juandi, Dadang (Fakultas Keguruan dan Ilmu Pendidikan Universitas Singaperbangsa, 2022)
This study aims to re-analyze Realistic Mathematics Education (RME) learning on students' mathematical creative thinking skills and then the results of the analysis from these studies are combined and obtained an overall conclusion. The method used in this study is the Systematic Literature Review (SLR) method. The SLR method is used to identify, review, evaluate, and interpret all available research with topic areas of interest to phenomena, with specific relevant research questions. With the use of the SLR method, a systematic review and identification of journals can be carried out, which in each process follows the steps or protocols that have been set. Data collection is done by searching journals and proceedings indexed by Scopus in the last 10 years with the keywords used in this search are